SPECIAL AND DIFFERENTIAL TREATMENT (SDT) IN THE WTO AGREEMENTS: A RULE-BASED APPROACH - Maulia Martwenty Ine (MIZAN, Jurnal Ilmu Hukum, 2023)
Members of the World Trade Organization (WTO) hold varying opinions regarding the status of developing countries as WTO members and Special and Differential Treatment (SDT), which reflects various perspectives on what constitutes fair treatment in the WTO. These discrepancies have now became more noticeable, which presents a problem for the organization. The definition of a developing country member, graduation, the efficacy of SDT, and technical support and capacity building have all been complicated topics explored in SDT discussions. Some of the WTO develop country members have suggested modifying the definition of developing country in regard to the Special and Differential Treatment (SDT) in the WTO agreements using a political and economic perspective. As the forum for negotiating agreements aimed at reducing barriers to international trade and ensuring a level playing field for all, the World Trade Organization (WTO) must be able to contribute to economic growth and development regardless of a country member's constitutional or socioeconomic structure, as well as foster peaceful cooperation among nations. The initiative of these members must, of course, be supported by the WTO, which role as the guarantor of the multilateral trading system, and as a bulwark against all forms of protectionism, while recognizing the developmental needs, as well as, the full WTO rights and obligations of members. The WTO can also, among other things, encourage all WTO members participating in plurilateral and multilateral initiatives to take a new approach to SDT in ongoing and future negotiations. Affirming that disputes concerning treaties, like other international disputes, should be settled by peaceful means and in conformity with the principles of justice and international law. By reviewing all laws and regulations that are connected to the status of developing countries as WTO members and Special and Differential Treatment (SDT), the author employs a "rule-based approach" in this article as set forth in article 31 of the Vienna Convention on the Law of Treaties, to analyze and respond to the question of what constitutes a member from a developing country as a beneficiary of SDT in order to achieve the goal of the World Trade Organization (WTO) which primary purpose is to open trade for the benefit of all